Varoluşsal hâl üzerinden ahlakiliği çerçeveleme denemesi: Hâlsel/düşünümsel etik - GÜLPINAR, MEHMET ALİ (My University, 2022)
Bu yazıda ahlâkilik, \"varoluşsal hâl\" üzerinden temellendirilebilir mi sorusuna cevap aranmaya çalışılmıştır. Ahlâkın \"akıl\" veya \"duygu\" yerine varoluşsal hâl üzerinden çerçevelendirilmesinin gerekçeleri ve imkânları tartışılmıştır. Bu arayışta karşıtlıklar üzerinden yürütülen tekçi veya ikili düşünce yaklaşımları yerine \"farkı var’layan birlik\" düşüncesi benimsenmiştir. Yine ahlâki düşünsellikleri \"akılsallık\" veya \"akılsallaştırma\"lar ile gerçekleştirmenin beraberinde getirdiği durumlar ve sonuçlar değerlendirilmiştir. Ötekine açık akılsallıkların ahlâkilikler ve ahlâki pratikler üretirken; ötekine kapalı akılsallaştırmaların daha çok ahlâkçılık ve kategorik \"iyi\" ve \"kötü\"ler üzerinden giden ahlâkçı pratiklerle sonuçlanması üzerine düşünülmüştür. Bu düşünüm iki örnek üzerinden açılmıştır: Pandemi sürecindeki \"aşı karşıtlığı/ kararsızlığı\" ve İstanbul Sözleşmesi etrafında yürütülen kadın ve aileye yönelik tartışmalar. Hem genel hem de İstanbul Sözleşmesi tartışmaları üzerinden \"kendilik ve şahsiyet olarak kadın\" bağlamında ahlâkilik ele alınmıştır. Akılsallıklar çerçevesinde oluşturulacak ahlâk sistemlerinin, teorilerinin ve toplumsal/kültürel ahlâki pratiklerin ana hatları ile çerçevesi çizilmeye çalışılmıştır. Bu çerçevelemenin merkezi kavramları şunlardır: \"arada’lık\", \"ahlâki mesafe\", \"yönelimsellik\", \"fark\", \"kendilik\" ve \"şahsiyet\". Bu kavramlar üzerinden \"hâlsel/düşünümsel etik\", kendilik etiği, şahsiyet etiği ve meydanda etik/meydan etiği ele alınmıştır.In this article, it has been tried to find an answer to the question of whether morality can be based on the \"existential state\". The rationale and possibilities of framing morality through the existential state instead of reason or emotion have been discussed. In this quest, the idea of unity with valued diversity has been adopted instead of monist or dualistic thinking approaches carried out through oppositions. Also, the situations and results brought about by realizing moral reflections with rationality and rationalization have been evaluated. The fact that rationalities open to the \"other\" produce moralities and moral practices, while rationalizations closed to the \"other\" result in moralistic practices that go through moralism and categorical \"good\" and \"evil\" have been thought over. This reflection has been expanded through two examples: \"vaccine opposition/ indecision\" during the pandemic process and the discussions about women and families carried on over the Istanbul Convention. Morality has been tackled in the context of \"woman as self and personality\", both in general and through various discussions over the Istanbul Convention. The moral systems, theories and social/ cultural moral practices that are to be formed within the framework of open rationalities have been tried to be outlined. The central concepts of this framing are: \"inbetweenness\", \"moral distance, \"intentionality\", \"diversity/ distinctness\", \"self\" and \"personality\". Through these concepts, \"existentially stative/ reflective ethics\", selfhood and ethics, personalistic ethics and ethics in agora have been discussed.

: In this article, it has been tried to find an answer to the question of whether morality can be based on the “existential state”. The rationale and possibilities of framing morality through the existential state instead of reason or emotion have been discussed. In this quest, the idea of unity with valued diversity has been adopted instead of monist or dualistic thinking approaches carried out through oppositions. Also, the situations and results brought about by realizing moral reflections with rationality and rationalization have been evaluated. The fact that rationalities open to the “other” produce moralities and moral practices, while rationalizations closed to the “other” result in moralistic practices that go through moralism and categorical "good" and "evil" have been thought over. This reflection has been expanded through two examples: “vaccine opposition/ indecision” during the pandemic process and the discussions about women and families carried on over the Istanbul Convention. Morality has been tackled in the context of "woman as self and personality", both in general and through various discussions over the Istanbul Convention. The moral systems, theories and social/ cultural moral practices that are to be formed within the framework of open rationalities have been tried to be outlined. The central concepts of this framing are: “inbetweenness”, “moral distance, “intentionality”, “diversity/ distinctness”, “self” and "personality". Through these concepts, “existentially stative/ reflective ethics”, selfhood and ethics, personalistic ethics and ethics in agora have been discussed.
Trying to frame morality over existential state: Stative/reflective ethics
Keywords: Sosyal ve Beşeri Bilimler; Felsefe; Diğer; Social Sciences and Humanities; Philosophy; Other; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; FELSEFE; BİLİM TARİHİ VE FELSEFESİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; PHILOSOPHY; HISTORY & PHILOSOPHY OF SCIENCE; Bilim Tarihi ve Felsefesi; Sosyal Bilimler ve Beşeri Bilimler; History and Philosophy of Science; Social Sciences & Humanities; Varoluş Felsefesi; arada’lık; fark; ahlâki mesafe; kendilik; şahsiyet; meydanda etik; Existential philosophy; in-betweenness; diversity/distinctness; moral distance; self; personality; ethics in agora